Upaya Meningkatkan Kompetensi Pedagogik Guru dalam Merencanakan dan Melaksanakan Pembelajaran Daring Melalui Supervisi Berkelanjutan - Riyo Darminto (Journal on Education, 2021)
The main purpose of this action research is to determine the effect of continuous supervision on improving the pedagogic competence of teachers in Planning and Implementing Online Learning at SDN Wonokusumo VI/45 Surabaya. In addition, because there are other alternative actions, this action research also aims to determine the class teacher's teaching preparation and the suitability, accuracy and integration of the online learning plans that have been prepared. Online or online learning is considered a solution for teaching and learning activities to continue in the midst of the corona pandemic. Online learning is learning without face to face directly between teachers and students, but is done online. Learning is done through video conferencing, e-learning or distance learning. Although it has been agreed, this method is controversial. For teachers, the online learning system is only effective for assignments. They consider that to make students understand the material, the online method is considered difficult. The implementation of continuous supervision in an effort to improve the pedagogic competence of teachers in Planning and Implementing Online Learning was carried out on 14 teachers at SDN Wonokusumo VI/45 Surabaya through a mechanism of 2 cycles, each of which used 11 effective school days. Cycle I, which was held on August 1-15, 2021, achieved 21% completeness in the poor category, while in cycle II, which was held on August 16-31, 2021, it was able to achieve 100% cycle completion in the very good category. From these results, the authors convey that the implementation of continuous supervision is very effective in improving the pedagogic competence of teachers in Planning and Implementing Online Learning at SDN Wonokusumo VI/45 Surabaya. The increase in pedagogic competence is only limited to aspects of planning and implementing online learning and several other factors that influence besides continuous supervision are the quality of online learning plans, the existence of supporting school infrastructure and training.